Histological and biochemical serum effects of alpha-tocopherol on ischemia/reperfusion-related injuries induced in the pelvic limb of rats - Silva,Marcelo Gomes da (2005)
PURPOSE: To evaluate the protective action of alpha-tocopherol in ischemia/reperfusion injuries of pelvic member of rats. METHODS: Thirty adult male rats of the Wistar strain were randomized into three experimental groups of 10: Group I - control group with no ischemia or reperfusion. Groups II and III - four hours of ischemia and of hours of reperfusion by means of clamping of the infrarenal aorta. The animals of Group II were treated with saline and those of Group III were treated with i.v. alpha-tocopherol (50 mg/kg). Parameters studied were biopsies of the soleus muscle, dosing of creatine phosphokinase, lactate dehydrogenase, potassium, calcium and arterial blood gasometry. RESULTS: The results of biopsies of the soleus muscles studied by optical microscopy, were not significant in terms of presence of edema among the three groups studied. Variables inflammation and necrosis were not observed, therefore cannot be statistically analyzed. As to dosing of calcium and lactate dehydrogenase, the pH, pO2 and pCO2 values were not significant for all groups studied. We observed that the levels of potassium (Group II > Group I, Fcalculated = 5.84; Fcritical = 3.33), creatine phosphokinase (Group II > Groups I and III, Hcalculated = 13.92; Hcritical = 5.99) and bicarbonate (Groups I and III > Group II, Hcalculated = 11.98; Hcritical = 5.99) presented significant results among groups. CONCLUSION: From the serum biochemical perspective, the treatment with alpha-tocopherol has attenuated the metabolic injuries in the ischemia/reperfusion syndrome in this experimental model.